Electrohydrodynamic printing as a method to micropattern large titanium implant surfaces with photocrosslinkable structures - Pokorny, Marek; Klemes, Jan; Zidek, Ondrej; Dollinger, Camille; Ozcebe, Gulberk; Singh, Sonali; Veleby, Vladmir; Ghaemmaghami, Amir M.; Wolfova, Lucie; Vrana, Nihal Engin (IOP Publishing, 2017)
Metallic implants are widely used in orthopaedic and orthodontic applications. However, generally surface treatment of the metallic surfaces is necessary to render them more biologically active. Herein, we describe a direct write printing method to modify metallic implant surfaces with biocompatible polymers with microscale precision. Application of polymeric micropatterns on metallic implant surfaces can (i) improve their interaction with the host tissue, (ii) enable the delivery of growth factors, antibiotics, anti-inflammatory cytokines etc from the implant surface and (iii) can control the immune responses to the implant via controlling the attachment of immune cells, such as macrophages. Surface patterns with a resolution of less than 50 μm can be created using an electro hydrodynamic (EHD) printing, a template-free and single-step process. We present a revised EHD printing method for the deposition of parallel strips of photocrosslinkable, cell adhesive polymeric composites with spacing of around 20 μm onto medical grade titanium substrates. Optimization of voltage, feeding rate and collection speed resulted in regular structures via very rapid movement of the grounded rotating collector driven to equivalent of the linear surface speed of above 100 cm s−1. In the experimental part a mixture of chemically modified PEG /gelatin was deposited onto a conductive titanium substrate with different surface pretreatments with an area of 400 mm2. Acid etched or UV treated titanium surfaces improved the stability of the printed structures. Polymeric lines induced temporary orientation of human monocytes (THP-1) and induced a thicker cell multilayer formation by 3T3 fibroblasts (p < 0.05). Staining of the monocytes for M1(CD80) and M2 (CD206) macrophage markers on the patterned surface showed mixed populations with higher anti-inflammatory cytokine secretion compared to tissue culture plastic control. The results demonstrate the suitability of this method for the preparation of biomaterials with structured surfaces on large areas and with desired chemical composition.